PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT GIGI MENGGUNAKAN ALGORITMA BAYES - Sri Ngudi Wahyuni; Lila Garjita (Universitas Alma Ata, 2019)
Dental disease is a health problem in Indonesia, many people complain aboutit. In 2013 Indonesia's basic health research that 25.9% of Indonesia'spopulation had dental and mouth problems. The public awareness to maintaindental and oral health is still low at around 13.1%. In addition, there is a lackof a number of dentists, causing the high cost of dental examinations. Theexpert system of Dental Disease Diagnosis System is a solution which can todetect symptoms of dental disease early before go to doctors.The Bayesalgorithm is one of methods which efisien to use in expert system fordeveloping it. The bayes algorithm is accurate to diagnose early dentaldiseases, by entering a diagnosis - an alternative probability value of thedisease and symptoms obtained from an expert.